Landfill Leachate Treatment by Electrocoagulation and Fiber Filtration: Li et al. (1st November 2017) - Li, Runwei; Wang, Boya; Owete, Owete; Dertien, Joe; Lin, Chen; Ahmad, Hafiz; Chen, Gang
ABSTRACT: : Landfilling is widely adopted as one of the most economical processes for solid waste disposal. At the same time, landfill leachate is also a great environmental concern owing to its complex composition and high concentrations of contaminants. This research investigated electrocoagulation and fiber filtration for the treatment of landfill leachate. Besides electrical current (i.e., current density) and reaction time, pH played a very important role in arsenic and phosphorus removal by electrocoagulation. The combination of electrocoagulation with fiber filtration achieved a 94% chemical oxygen demand (COD), 87% arsenic, 96% iron, and 86% phosphorus removal. During electrocoagulation, the micro‐particles that could not be settled by gravity were removed by the first stage of fiber filtration. Organic contaminants in the leachate were further removed by biodegradation in the second stage of fiber biofiltration.